Bovicin HC5, a Lantibiotic Produced by Streptococcus bovis HC5, Catalyzes the Efflux of Intracellular Potassium but Not ATP - Mantovani, Hilário C. (American Society for Microbiology (ASM), 2008)
Bovicin HC5, a broad-spectrum lantibiotic produced by Streptococcus bovis HC5, catalyzed the efflux of intracellular potassium from Streptococcus bovis JB1, a sensitive strain. The level of ATP also decreased, but this decline appeared to be caused by the activity of the F(1)F(0) ATPase rather than efflux per se.